2014
DOI: 10.1111/jog.12347
|View full text |Cite
|
Sign up to set email alerts
|

Social oocyte freezing: A survey among Singaporean female medical students

Abstract: Aim: Social oocyte freezing has gained increasing interest worldwide. We conducted a cross-sectional survey on 129 female medical students in Singapore to assess their mindset and attitudes toward fertility and social oocyte freezing. Methods: An anonymous online survey was conducted among female medical students in Singapore. The desired sample size was 100 participants. Their awareness of the existence of social oocyte freezing was first assessed. An information leaflet was provided subsequently, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
4
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 7 publications
6
66
4
4
Order By: Relevance
“…Our data were collected just a few months after Apple and Facebook publicly agreed to cover the expenses of oocyte freezing for their female employees in the USA as well as during the midst of a debate in the medical and lay field about the use of the technology to delay childbirth for career reasons and the role of the society regarding this topic [37][38][39][40][41][42][43][44][45]. In contrast to a study from Singapore where 70 % of female medical students would consider this an option for family planning, only about half of our study participants knew about the principle of oocyte freezing, and 12 % would consider this technology as an option for themselves [20]. In two recent surveys 53-64 % of the 14-30-year-old German participants had a positive attitude towards oocyte freezing, and only one third of them would use it [46,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data were collected just a few months after Apple and Facebook publicly agreed to cover the expenses of oocyte freezing for their female employees in the USA as well as during the midst of a debate in the medical and lay field about the use of the technology to delay childbirth for career reasons and the role of the society regarding this topic [37][38][39][40][41][42][43][44][45]. In contrast to a study from Singapore where 70 % of female medical students would consider this an option for family planning, only about half of our study participants knew about the principle of oocyte freezing, and 12 % would consider this technology as an option for themselves [20]. In two recent surveys 53-64 % of the 14-30-year-old German participants had a positive attitude towards oocyte freezing, and only one third of them would use it [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported knowledge gaps concerning fertility awareness, parenting attitudes, and specific factors influencing fertility in students in Europe [10][11][12][13][14][15][16][17], Asia [18][19][20], Africa [21], Australia [22,23], Canada [24,25], and the USA [26,27]. These studies have investigated the knowledge of young people or students, but little is known about the attitude of students towards ART and oocyte freezing as well as the differences in knowledge about fertility in special groups, e.g., medical and non-medical students and between sexes.…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al [10] conducted a cross-sectional survey on 129 female medical students in Singapore to assess their mindset and attitudes toward fertility and social oocyte freezing. An anonymous online survey was conducted among female medical students in Singapore.…”
Section: Discussionmentioning
confidence: 99%
“…Of the total, 89.9 % considered themselves too old for pregnancy after the age of 35 years, 37.2 % would delay family planning for their career, 45.7 % would consider social oocyte freezing to postpone family planning for their career, 46.5 % would consider oocyte freezing if they had no suitable partners yet, 50.4 % may consider freezing their eggs after the age of 30 years and 71.3 % may be more amenable to oocyte freezing if government subsidy is available. The authors hypothesized that social oocyte freezing may be a viable option for single young women who wish to delay childbearing for ''reproductive insurance,'' so long as this is done with appropriate informed consent with nondirective counseling [10].…”
Section: Discussionmentioning
confidence: 99%
“…Surveys on public attitudes show, that elective egg cryopreservation is viewed more negatively than medical egg cryopreservation; and that the majority of the women in the examined societies-which included Sweden, Belgium, US, Singapore-would not partake in the procedure themselves, or are uncertain (Lallemant et al 2016, Lewis et al 2016, Stoop et al 2011Hoodes-Wertz et al 2013;Tan et al 2014, Wennberget al 2016. In a small scale study for her MA thesis Keglovits (2015) studied Hungarian women's attitudes towards egg cryopreservation with the help of four focus groups.…”
Section: Overview Of Empirical Studies On Egg Cryopreservationmentioning
confidence: 99%